Comparative statistical analysis of service quality in turkish and romanian banking sectors : (at a company level) - Caiali, Meral (My University, 2007)
unknown
Keywords: Bankalar ve Bankacılık_Hizmet Kalitesi; Hizmet Kalitesi; İş Tatmini; Türkiye_Bankalar ve Bankacılık_Romanya; Türkiye_Hizmet Kalitesi_Romanya